Simultaneous effects of heat transfer and variable viscosity on peristaltic transport of casson fluid flow in an inclined porous tube - Manjunatha, Gudekote; Rajashekhar, V. Choudhari; Vaidya, Hanumesh; Prasad, Kerehalli Vinayaka (Zielona Góra: Uniwersytet Zielonogórski)
The present study investigates the combined effects of varying viscosity and heat transfer on a Casson fluid through an inclined porous axisymmetric tube in the presence of slip effects. The modeled governing equations are solved analytically by considering the long wavelength and small Reynolds number approximations. The numerical integration is employed to obtain pressure rise and frictional force.
Keywords: Darcy number; thermal slip; velocity slip; variable viscosity; yield stress